POLICIES AND PROCEDURES IN FEDERAL CIVILIAN PROCUREMENT. - Linnenberg, Clem C. (The Accounting Review, 1943)
Buying for the government is subject to a vast aggregate of statutes, Executive and administrative orders, legal interpretations by the General Accounting Office, and court decisions. Some rules, such as those relating to standardized specifications, have their parallel in private business enterprises. Others have, but only if one forgets that a rule-making power vested in Congress and a separate administrative responsibility vested in a department head are likely to afford much less flexibility of rules than exists where not only administrative responsibility but also a generous measure of rule-making power are vested in a single manager. The contrast is all the greater if the business concern which the manager runs is not itself a body of such great size as to have the sort of complexity which characterizes governmental organization. Funds for procurement or for non-procurement purposes are usually made available in and for a single fiscal year. In the enforcement of the laws with which Federal procurement is hedged about, the General Accounting Office figures much more largely than the courts. Infractions of those laws usually are less classifiable as criminality than as inept or culpable administration, or as an admirably motivated if indiscreet effort to get a job done even at the cost of scissoring some red tape.